Hubungan Pengetahuan dan Sikap Ibu Hamil terhadap Mual Muntah Kehamilan dengan Waktu Mual Muntah Kehamilan di PUSKESMAS Sumobito Kota Jombang: Relationship between Knowledge and Attitude of Pregnant Women on Nausea and Vomiting Pregnancy with Time of Nausea and Vomiting in Pregnancy at PUSKESMAS Sumobito, Jombang City - Mudlikah, Siti; D H, Sutjiati; Ningrum, Neny Ilmia (Jurnal Kebidanan Midwiferia, 2019)
Nausea vomiting (emesis gravidarum) 50-60% occurs at the beginning of pregnancy trimester I. causes of increased estrogen, progesterone, and the release of human chorionic gonadothropine. Excessive emesis gravidarum is at risk of hyperemisis gravidarum which threatens the life of pregnant women. placenta. Purpose of the study: To determine the relationship between knowledge and attitudes of pregnant women to emesis gravidarum at Sumobito Health Center, Jombang Regency. Obeservational, cross sectional, total population of 34 first trimester pregnant women statistics Spearman Rank Correlation Test and somers test. Pregnant women had good knowledge of 15 (44.1%), sufficient knowledge 13 (38.2%), and insufficient knowledge 6 (17.7%). While being positive 24 (71%) and being negative 10 (29%), Rank Spearman test. Knowledge α = 0.005. P value = 0.216. The attitude test somers a = 0.05 P value = 0.954. There was no correlation between knowledge and the incidence of emesis gravidarum and there was no correlation between the attitude of pregnant women and the incidence of emesis gravidarum.